PDX1-E178G Mutation: Its Impact on Protein Structure and Insulin Gene Regulation in the Cause of Type-2 Diabetes Mellitus - Ningrum Wahyuni; Melviana Lubis (Faculty of Medicine and Health Universitas Muhammadiyah Jakarta, 2025)
Background: Pancreatic and duodenal homeobox 1 (PDX1) is a key transcription factor for pancreatic β-cell differentiation and insulin gene regulation. Mutations in PDX1, such as E178G, have been linked to monogenic diabetes, including MODY4. Understanding the structural and functional consequences of these mutations is critical for advancing diagnostic and therapeutic strategies. Methods: This study employed an in silico approach to assess the impact of the E178G missense mutation on PDX1. Bioinformatics tools were used to evaluate physicochemical properties, secondary and tertiary structure, residue-level interactions, and subcellular localization. Wild-type and mutant models were compared using ProtParam, PSIPRED, SWISS-MODEL, PyMOL, and DeepLoc. Results: The E178G mutation did not affect the overall structure or nuclear localization of PDX1. However, secondary structure prediction revealed a localized decrease in α-helix stability near the mutation site. Tertiary structure modeling and visualization indicated the loss of key polar interactions, which may weaken the DNA-binding capacity of the homeodomain. Discussion: Although nuclear localization remains intact, disruption of structural integrity within the homeodomain suggests impaired transcriptional activity. This supports the hypomorphic nature of the E178G variant, which may lead to partial β-cell dysfunction. The findings are consistent with previous reports linking similar PDX1 mutations to MODY4 phenotypes. Conclusion: The E178G mutation in PDX1 is predicted to cause subtle but functionally relevant structural changes, potentially impairing its role in insulin gene regulation. These results reinforce the value of in silico analysis in understanding the pathogenic mechanisms of genetic variants and guiding precision medicine in monogenic diabetes.